Antihypertensive Drugs and Cancer Risk. (20th May 2022) - Kidoguchi, Satoshi; Sugano, Naoki; Yokoo, Takashi; Kaneko, Hidehiro; Akazawa, Hiroshi; Mukai, Mikio; Node, Koichi; Yano, Yuichiro; Nishiyama, Akira
Abstract: Hypertension is the most prevalent comorbidity in cancer patients. Consequently, many cancer patients are prescribed antihypertensive drugs before cancer diagnosis or during cancer treatment. However, whether antihypertensive drugs affect the incidence, treatment efficacy, or prognosis of cancer remains unanswered. For instance, renin–angiotensin and β-adrenergic signaling may be involved not only in blood pressure elevation but also in cell proliferation, angiogenesis, and tissue invasion. Therefore, the inhibition of these pathways may have beneficial effects on cancer prevention or treatment. In this article, we reviewed several studies regarding antihypertensive drugs and cancer. In particular, we focused on the results of clinical trials to evaluate whether the use of antihypertensive drugs affects future cancer risk and prognosis. Unfortunately, the results are somewhat inconsistent, and evidence demonstrating the effect of antihypertensive drugs remains limited. We indicate that the heterogeneity in the study designs makes it difficult to clarify the causal relationship between antihypertensive drugs and cancer. We also propose that additional experimental studies, including research with induced pluripotent cells derived from cancer patients, single-cell analyses of cancer cell clusters, and clinical studies using artificial intelligence electronic health record systems, might be helpful to reveal the precise association between antihypertensive drugs and cancer risk. Graphical Abstract: